Rethinking international commercial arbitration : towards default arbitration - Cuniberti, Gilles, 1971- (Edward Elgar Publishing, 2017)
This innovative book proposes a fundamental rethink of the consensual foundation of arbitration and argues that it should become the default mode of resolution in international commercial disputes. The book first discusses the most important arguments against this proposal and responds to them. In particular, it addresses the issue of the legitimacy of arbitrators and the compatibility of the idea with guarantees afforded by European human rights law and US constitutional law. The book then presents several models of non-consensual arbitration that could be implemented to afford neutral adjudication in disputes between parties originating from different jurisdictions, to offer an additional alternative forum in the doctrine of forum non conveniens or to save judicial costs. The first dedicated exploration into the groundbreaking concept of default arbitration, Rethinking International Commercial Arbitration will appeal to scholars, students and practitioners in arbitration and international litigation.